Animal Models in Diabetes Research - Joost, Hans-Georg (Methods in molecular biology, 2012)
The Non-Obese Diabetic (NOD) Mouse as a Model of Human Type 1 Diabetes -- Assessment of Diabetic Nephropathy in the Akita Mouse -- The BB Rat as a Model of Human Type 1 Diabetes -- Diabetes in Mice with Monogenic Obesity: The db/db Mouse and Its Use in the Study of Cardiac Consequences -- Pathophysiology and Genetics of Obesity and Diabetes in the New Zealand Obese Mouse: A Model of the Human Metabolic Syndrome -- The TALLYHO Mouse as a Model of Human Type 2 Diabetes -- Diet-Induced Diabetes in the Sand Rat (Psammomys obesus) -- Diabetes in Zucker Diabetic Fatty Rat -- The GK Rat: A Prototype for the Study of Non-Overweight Type 2 Diabetes? -- Experimentally Induced Rodent Models of Type 2 Diabetes -- Investigation and Treatment of Type 2 Diabetes in Nonhuman Primates -- Determination of Beta-Cell Function: Insulin Secretion of Isolated Islets -- Determination of Beta-Cell Function: Ion Channel Function in Beta Cells -- Measurement of Glucose Homeostasis In Vivo: Glucose and Insulin Tolerance Tests -- Measurement of Glucose Homeostasis In Vivo: Combination of Tracers and Clamp Techniques -- Measurement of Insulin Sensitivity in Skeletal Muscle In Vitro -- Beta-Cell Autoimmunity -- Positional Cloning of Diabetes Genes -- Retinal Digest Preparation: A Method to Study Diabetic Retinopathy -- Lineage Tracing of Pancreatic Stem Cells and Beta Cell Regeneration -- Genetic Lineage Tracing of Beta Cell Neogenesis.
Keywords: Tiermodell; Diabetes mellitus